2016
DOI: 10.3928/00989134-20160201-04
|View full text |Cite
|
Sign up to set email alerts
|

Memory Matters: A Mixed-Methods Feasibility Study of a Mobile Aid to Stimulate Reminiscence in Individuals With Memory Loss

Abstract: Reminiscence interventions are potentially effective in improving well-being of persons with memory loss (PWMLs) and may also enhance relationships with family and professional caregivers. Using a parallel convergent mixed-methods design, the feasibility of “Memory Matters” (MM), a mobile device application developed to promote reminiscence, was evaluated. Eighteen PWMLs and eight family members were enrolled from a long-term care facility and asked to use MM for 4 weeks. Participants were observed using MM at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 21 publications
2
38
0
1
Order By: Relevance
“…Although limited by the small sample sizes of some of the studies, the authors concluded that there were benefits to using information and communication technology (ICT) for reminiscence interventions. These benefits include access to rich and engaging multimedia reminiscence materials [ 13 , 14 ], opportunities for people living with dementia to participate in social interactions and take ownership of conversations [ 15 , 16 ], and a reduction in motor deficit-related barriers when interacting with media [ 16 , 17 ]. In the abovementioned review [ 12 ], 10 reviewed papers reported on the use of “reminiscence kits” that featured a technological component.…”
Section: Introductionmentioning
confidence: 99%
“…Although limited by the small sample sizes of some of the studies, the authors concluded that there were benefits to using information and communication technology (ICT) for reminiscence interventions. These benefits include access to rich and engaging multimedia reminiscence materials [ 13 , 14 ], opportunities for people living with dementia to participate in social interactions and take ownership of conversations [ 15 , 16 ], and a reduction in motor deficit-related barriers when interacting with media [ 16 , 17 ]. In the abovementioned review [ 12 ], 10 reviewed papers reported on the use of “reminiscence kits” that featured a technological component.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies focused on reminiscence‐based activities with multimedia content by using mobile technology with interactive games, Memory Matters (Hamel et al . ) or Computer Interactive Reminiscence and Conversation Aid (CIRCA) for conversation and engagement with persons with DAT (Alm et al . , Astell et al .…”
Section: Resultsmentioning
confidence: 98%
“…, Hamel et al . ). An Involvement Measure (Murphy and Oliver ) and decisional capacity questionnaire (Chang ) were developed to measure decision‐making skills in interactions by adapting questions from other tools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an exciting time of technology innovation that shows no signs of slowing. Wearable camera systems for family caregivers of individuals with dementia (Matthews et al, 2016), mobile apps to promote reminiscence (Hamel, Sims, Klassen, Havey, & Gaugler, 2016), and information visualization to improve engagement in the advance directives process (Woollen & Bakken, 2016) are some of the recent examples highlighted in the Journal of Gerontological Nursing. There are so many opportunities for nurses to make a positive impact on the lives of older adults and their families through technology.…”
mentioning
confidence: 99%